Relationship of bisphenol A substitutes bisphenol F and bisphenol S with adiponectin/leptin ratio among children from the environment and development of children cohort - Hye Jin Lee; Yun Jeong Lee; Youn-Hee Lim; Hwa Young Kim; Bung-Nyun Kim; Johanna Inhyang Kim; Yong Min Cho; Yun-Chul Hong; Choong Ho Shin; Young Ah Lee (Environment International, 2024)
Background: Bisphenol A (BPA) is known as an obesogenic endocrine disruptor. Bisphenol S (BPS) and F (BPF) are substitutes that have recently replaced BPA. Objectives: To investigate the relationships of urinary bisphenols (BPA, BPS and BPF) with adiposity measurements (obesity, BMI z-score, and fat mass), serum adipokine levels (adiponectin and leptin), and adiponectin/leptin ratio (A/L ratio) in 6- and 8-year-old children. Methods: A total of 561 children who participated in the Environment and Development of Children cohort (482 and 516 children visited at age 6 and 8, respectively) at Seoul National University Children’s Hospital during 2015–2019 were included. Urinary BPA levels were log-transformed. BPS levels were categorized into three groups (non-detected, lower-half, and higher-half of detected), and BPF levels were classified into two groups (non-detected and detected). Results: The urinary BPS higher-half group had a higher BMI z-score (β = 0.160, P = 0.044), higher fat mass (β = 0.104, P < 0.001), lower adiponectin concentration (β =- 0.069, P < 0.001), higher leptin concentration (β = 0.360, P < 0.001), and lower A/L ratio (β =- 0.428, P < 0.001) compared with the non-detected group. The urinary BPF-detected group had a higher fat mass (β = 0.074, P < 0.001), lower adiponectin concentration (β =- 0.069, P < 0.001), higher leptin concentration (β = 0.360, P < 0.001), and lower A/L ratio (β =- 0.428, P < 0.001) compared with the non-detected group. The BPA levels showed no consistent associations with outcomes, except for isolated associations of BPA at age 6 with a higher BMI z-score at age 6 (P = 0.016) and leptin at age 8 (P = 0.021). Conclusions: Increased exposure to BPS and BPF is associated with higher fat mass and leptin concentration, lower serum adiponectin, and lower A/L ratio in children. These findings suggest potential adverse effects of BPA substitutes on adiposity and adipokines. No consistent association of BPA exposure with outcomes could be partly explained by the decreasing BPA levels over time.